2017
DOI: 10.35784/acs-2017-21
|View full text |Cite
|
Sign up to set email alerts
|

New Extrusion Process for Producing Twist Drills Using Split Dies

Abstract: The paper presents a new extrusion process for producing twist drills using split dies. The design of the dies is described, where the profile of the flute-forming element is the same as the profile of the flute on the plane inclined to the drill axis at an angle equal to the helix angle. The proposed method for the extrusion of twist drills by the new type of dies is verified by numerical modeling. Three cases of the extrusion process are modelled, each with a different position of the flute-forming element r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The experimental result revealed that a relatively high forming precision and relatively low damage value of 304 stainless was obtained under the rolling depth of 3.3 mm and formation speeds below 15 mm/s. Bulzak et al [35,36] analysed the forward extrusion forming (FEF) process of twist drills, as shown in Figure 7. During the extrusion process, the starting materials were heated to a suitable temperature for hot forming.…”
Section: Solid Plastic Forming Processmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental result revealed that a relatively high forming precision and relatively low damage value of 304 stainless was obtained under the rolling depth of 3.3 mm and formation speeds below 15 mm/s. Bulzak et al [35,36] analysed the forward extrusion forming (FEF) process of twist drills, as shown in Figure 7. During the extrusion process, the starting materials were heated to a suitable temperature for hot forming.…”
Section: Solid Plastic Forming Processmentioning
confidence: 99%
“…The results demonstrated the feasibility of the production of either hollow or solid screw rods with a high uniformity in wall thickness by the RCFF process. They found that when the belt height where the die works Bulzak et al [35,36] analysed the forward extrusion forming (FEF) process of twist drills, as shown in Figure 7. During the extrusion process, the starting materials were heated to a suitable temperature for hot forming.…”
Section: Solid Plastic Forming Processmentioning
confidence: 99%